Adobe Photoshop CC for photographers : 2015 release : a professional image editor's guide to the creative use of Photoshop for the Macintosh and PC /: 2015 release : a professional image editor's guide to the creative use of Photoshop for the Macintosh and PC. (2016) - Evening, Martin
No abstract available